Physical processes as a result of concrete concrete in dry-hot climate conditions - Khakimov Sh.A; Muminov K.K; Cholponov O; Mamadov B.A; Maqsud oglu Bakhtiyor; D.Akramova (International Journal on Human-Computing Studies, 2021)
In this article, it is giveh the issues of heat processing of concrete in winter and the results of exheriments of the effects of the water cement of the concrete